From the Tunnels into the Treetops: New Lineages of Black Yeasts from Biofilm in the Stockholm Metro System and Their Relatives among Ant-Associated Fungi in the Chaetothyriales - Réblová, Martina; Hubka, Vit; Thureborn, Olle; Lundberg, Johannes; Sallstedt, Therese; Wedin, Mats; Ivarsson, Magnus (PloS one, 2016)
Rock-inhabiting fungi harbour species-rich, poorly differentiated, extremophilic taxa of polyphyletic origin. Their closest relatives are often well-known species from various biotopes with significant pathogenic potential. Speleothems represent a unique rock-dwelling habitat, whose mycobiota are largely unexplored. Isolation of fungi from speleothem biofilm covering bare granite walls in the Kungsträdgården metro station in Stockholm yielded axenic cultures of two distinct black yeast morphotypes. Phylogenetic analyses of DNA sequences from six nuclear loci, ITS, nuc18S and nuc28S rDNA, rpb1, rpb2 and β-tubulin, support their placement in the Chaetothyriales (Ascomycota). They are described as a new genus Bacillicladium with the type species B. lobatum, and a new species Bradymyces graniticola. Bacillicladium is distantly related to the known five chaetothyrialean families and is unique in the Chaetothyriales by variable morphology showing hyphal, meristematic and yeast-like growth in vitro. The nearest relatives of Bacillicladium are recruited among fungi isolated from cardboard-like construction material produced by arboricolous non-attine ants. Their sister relationship is weakly supported by the Maximum likelihood analysis, but strongly supported by Bayesian inference. The genus Bradymyces is placed amidst members of the Trichomeriaceae and is ecologically undefined; it includes an opportunistic animal pathogen while two other species inhabit rock surfaces. ITS rDNA sequences of three species accepted in Bradymyces and other undescribed species and environmental samples were subjected to phylogenetic analysis and in-depth comparative analysis of ITS1 and ITS2 secondary structures in order to study their intraspecific variability. Compensatory base change criterion in the ITS2 secondary structure supported delimitation of species in Bradymyces, which manifest a limited number of phenotypic features useful for species recognition. The role of fungi in the speleothem biofilm and relationships of Bacillicladium and Bradymyces with other members of the Chaetothyriales are discussed.
Keywords: sekvence nukleotidů; DNA, Fungal; Nucleic Acid Conformation; RNA-polymerasa II; Bayes Theorem; fylogeneze; RNA Polymerase II; Phylogeny; ribozomální DNA; Fungal Proteins; Sequence Alignment; Ants; sekvenční seřazení; DNA fungální; konformace nukleové kyseliny; Animals; Biofilms; zvířata; Sweden; Bayesova věta; Ascomycota; biofilmy; Base Sequence; tubulin; DNA, Ribosomal; Formicidae; fungální proteiny; Tubulin; Švédsko